THE EFFECT OF LOADS SUPERPOSITION ON TECHNICAL STRUCTURES, ENVIRONMENT AND LIVING ORGANISMS - VALERIU V. JINESCU; IONELA MIHAELA ROȘU MARIN; GEORGE JINESCU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The current state of calculation the result of the superposition of loads, or their effects, on a material body is analyzed. The limits of the current calculation methods, based on strength theories, in the case of technical structures are shown. The results of experimental research that refer, in general, to the superposition of two loads of the same nature and without addressing problems of loads of a different nature (mechanical, chemical, electrical, magnetic, radioactive etc.), in the case of technical structures and the environment is analyzed. Starting from the principle of critical energy, which is based on the concepts of the total specific energies’ participation of the loads and of the critical participation, general relations are deduced for these concepts, in the case of the nonlinear behavior of matter, as a function of power. These results are applied to the calculation of the superposition of loads of different nature on a technical structure, the environment and living organisms, taking into account the deterioration of matter. The influence of the loading speed (static, shock ...) is taken into account based on the value of the exponent in the behavior law, which was not possible in the previous calculation methods. From the analysis of the results obtained in the paper, it is found the utility and the high degree of generality of the principle of critical energy and of the concept of the specific energy participation.